Ocena ryzyka, okoliczności i następstwa upadków oraz ich uwarunkowania wśród mieszkańców domu pomocy społecznej = Risk assessment, circumstances and consequences of falls and their conditioning among social welfare home inhabitants - Adrian Bartoszek; Katarzyna Kocka; Agnieszka Bartoszek; Barbara Ślusarska; Izabela Dudek; Kamila Jamrozik (Kazimierz Wielki University, 2016)
Bartoszek Adrian, Kocka Katarzyna, Bartoszek Agnieszka, Ślusarska Barbara, Dudek Izabela, Jamrozik Kamila. Ocena ryzyka, okoliczności i następstwa upadków oraz ich uwarunkowania wśród mieszkańców domu pomocy społecznej = Risk assessment, circumstances and consequences of falls and their conditioning among social welfare home inhabitants. Journal of Education, Health and Sport. 2016;6(8):257-266. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60513 http://ojs.ukw.edu.pl/index.php/johs/article/view/3757       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.07.2016. Revised 08.08.2016. Accepted: 18.08.2016.     Ocena ryzyka, okoliczności i następstwa upadków oraz ich uwarunkowania wśród mieszkańców domu pomocy społecznej Risk assessment, circumstances and consequences of falls and their conditioning among social welfare home inhabitants Adrian Bartoszek1, Katarzyna Kocka2, Agnieszka Bartoszek2, Barbara Ślusarska2, Izabela Dudek3, Kamila Jamrozik4   1 Student Kierunku Lekarskiego, Wydział Lekarski, Uniwersytet Medyczny w Łodzi 2 Zakład Medycyny Rodzinnej i Pielęgniarstwa Środowiskowego, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 3 NZOZ DIAVERUM, ul. 30 Stycznia 57/58, 83-110 Tczew 4 Centrum Medyczne DYNMED, ul. Rynek 10, 36-065 Dynów     Background Falls are one of main causes of injuries and disability among people after 65 years old and also of accidental deaths and nowadays are essential public health problems. Objective The aim of research was assessment of falls risk, circumstances and falls corollary and their conditioning among inhabitants of social welfare home. Material and methods Researches were done among 43 inhabitants of social welfare home in podkarpackie voivodeship from December 2015 to February 2016. Assessment of fall risk was done by Tinetti test (POMA). Results Fall risk among social welfare home inhabitants is big. Large falls risk refer to 59,5 % and danger of fall risk refer to 31%. In the last year 33,3 % fell once,  28,6% more than once, post-fall syndrome concern 74,1 %. Falls usually took place except place of living (60%) and 19% on the social welfare area. Most common physical consequences of falls were bruises (42,9%). High risk of falls concern people older than 75 years old, women and people with elementary education living over 3 years in social welfare home (66,7%). Conclusions • According to Tinetti test, large risk of fall concern 60 % respondents and danger of fall concern 31% respondents living in social welfare home. • High index of falls was set, because 62% inhabitants in the year before research fell once or more. Mostly falls were outside social welfare house. • Most common mental consequence of falls was post-fall syndrome (74%) and physical - bruises(43%). • High risk of falls was connected with age, gender, education, time spent in social welfare home years and analysed risk factors. • High risk of falls is essentially connected with polypharmacy, presence of defect of ear and eye, one or more falls in the last year and post-fall syndrome.   Key words: falls, risk factors, elderly people, social welfare home.       Wprowadzenie Upadki są jedną z głównych  przyczyn urazów i  niepełnosprawności wśród osób po 65 r.ż. a także przypadkowych zgonów i są obecnie istotnym problemem zdrowia publicznego Cel pracy Celem pracy była ocena ryzyka, okoliczności i następstw upadków oraz ich uwarunkowań  wśród mieszkańców domu pomocy społecznej Materiał i metoda Badania przeprowadzono  wśród osób 43 mieszkańców domu pomocy społecznej w województwie podkarpackim w okresie od grudnia 2015 do lutego 2016 roku.  Oceny ryzyka upadków dokonano za pomocą standaryzowanego narzędzia całościowej oceny geriatrycznej: Testu  Tinetti (POMA).  Wyniki Ryzyko upadków wśród mieszkańców DPS jest duże. U 59,5% występuje duże ryzyko upadku, zagrożenie upadkiem dotyczy 31%. W ciągu 12 miesięcy przed badaniem 1 raz upadło 33,3% badanych, natomiast 28,6%  powyżej 1 razu, zespół poupadkowy - dotyczy 74,1% badanych. Upadek w większości wystąpił poza miejscem zamieszkania (60%) natomiast wśród 19% osób na terenie dps. Najczęstszą fizyczną konsekwencją upadków były siniaki (42,9%). Wysokie ryzyko upadków dotyczyło osób mających 75 lat i więcej , kobiet, osób z wykształceniem podstawowym, mieszkających powyżej 3 lat w DPS (66,7%). Wnioski • U mieszkańców domu pomocy społecznej według testu Tinetti  duże ryzyko upadku dotyczy 60 % mieszkańców  a zagrożenie upadkiem  31% badanych.  • Stwierdzono wysoki wskaźnik upadków w badanej grupie, bowiem  prawie 62% podaje wystąpienie jednego i większej ilości upadków w ciągu 12 miesięcy przed badaniem, które w większości wystąpiły poza miejscem zamieszkania • Najczęstszą psychiczną konsekwencją upadków był zespół poupadkowy (74%), natomiast fizyczną- siniaki(43%). • Wysokie ryzyko upadków było związane z wiekiem , płcią , wykształceniem badanych, okresem pobytu w DPS i analizowanymi czynnikami ryzyka. • Wysokie ryzyko upadków mieszkańców DPS związane jest istotnie z terapią wielolekową, występowaniem wad  wzroku i słuchu, jednego i więcej  upadków w ciągu ostatniego roku oraz z obawą przed kolejnym upadkiem.   Słowa kluczowe: upadki, czynniki ryzyka, osoby starsze, dom pomocy społecznej.